KOMUNIKASI PEMBANGUNAN PARTISIPATIF DALAM PEMBERDAYAAN PURNA PEKERJA MIGRAN - Mulyana, Slamet; Octavianti, Meria (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2018)
The empowerment of Indonesian post-migrant workers (Purna PMI) is carried out continuously to reduce the numbers of Indonesians working abroad. Aside from programs of related agencies, the government also involves direct community participation. This study sought to describe the participatory development communication (PDC) of Forum Purna PMI in Desa Celak, Kecamatan Gununghalu, Kabupaten Bandung Barat. This study used case study approach to provide a complete and in-depth view of the subject under study. The nature of the subject was multi-source, with key informants representing bureaucrats, academics, community leaders and post-migrant workers. Data was collected through interviews, observations and literature study. The results showed that community involvement was an important factor in realizing community development communication. Direct involvement in the planning and implementation of empowerment programs in the village fosters the community awareness to build their village, to get a job, to improve their welfare and to not leave their village in order to be a migrant worker.